Employee engagement and performance: A systematic literature review - Błażej Motyka (International Journal of Management and Economics, 2018)
Scholars and practitioners indicate that low level of employee engagement at work is currently one of the most alarming global economic problems. The potential consequence of this phenomenon is declining work performance. Therefore, it becomes important to understand the concept of work engagement, its meaning for employees, and implications for employers. The article is a systematic review of the body of literature, presenting the results of research on the association between employee engagement and various performance categories. The paper's objective is to summarize prior studies based on their ordering and categorization, identify gaps in the current knowledge, and propose an agenda for future research. The article presents these findings in a synthetic manner, offering practical and academic implications arising therefrom. Results of the review indicate that, in the case of most peer-reviewed publications, a statistically significant relation between employee engagement and numerous categories and subcategories of performance was confirmed.
Keywords: J24; J53; 650; employee engagement; work engagement; process performance; outcome performance